Blocking p38 Signaling Reduces the Activation of Pro-inflammatory Cytokines and the Phosphorylation of p38 in the Habenula and Reverses Depressive-Like Behaviors Induced by Neuroinflammation - Zhao, Ya-wei; Pan, Yu-qin; Tang, Ming-ming; Lin, Wen-juan (Frontiers in Pharmacology, 2018)
Increasing evidence has demonstrated that neuroinflammation contributes to the development of depressive-like behaviours, in both animal models and human patients; however, the brain areas and signalling pathways involved are still elusive. Recent studies have suggested novel roles of the habenula in the onset of depression and other psychiatric disorders; however, there is no evidence for whether the habenula has a function in neuroinflammation-induced depression. Using an animal model of depression, which is induced by the repeated central administration of lipopolysaccharide (LPS), we examined whether cytokine expression and p38 signal activation in the habenula were involved in the depressive-like behaviours. Body weight, saccharin preference test, and tail suspension test were used to measure depressive-like behaviours. Immunohistochemistry, quantitative-polymerase chain reaction (q-PCR), and western blot were used to measure the expression of tumour necrosis factor-α (TNF-α), interleukin-10 (IL-10) and the phosphorylation of p38 in the habenula. The results showed that central LPS administration induced depressive-like behaviours, characterized by anhedonia in the saccharin preference test and increased immobility in the tail suspension test. Central LPS administration also significantly increased the p-p38 level in microglial cells and increased TNF-α expression in the habenula. Treatment with fluoxetine, a widely prescribed antidepressant, or SB203580, a p38-specific inhibitor, reversed the depressive-like behaviours, normalized the alterations in p-p38 and TNF-α levels and increased the levels of the anti-inflammatory cytokine IL-10 in the habenula. The present findings suggest that the habenula is involved in the pathophysiology of behavioural depression induced by neuroinflammation, and the p38 pathway may serve as a novel mechanism-based target for the treatment of inflammation-related depression.